Lakes near the glacier Maliy Azau on the Elbrus (Central Caucasus): dynamics and outbursts - M. D. Dokukin; A. V. Khatkutov (Лëд и снег)
The lake dynamics and the current state of them were analyzed on the basis of interpretation of aerial and satellite images of different years together with results of field surveys. Areas of six lakes existing in different years near the Maliy Azau Glacier had been determined. On August 22, 2011, the maximum area of one of the lakes was equal to 25.5 thousand m2. The first outburst was caused by the landslide deformations of the moraine massif forming a part of the lake basin, while the second one was a result of degradation of the lake ice dam and the water overflow on top of it. The present‑day lake dams (terminal‑moraine ramparts and medial moraine ridges) are the result of the Maliy Azau Glacier advance in 1990s. The revealed feature of the lake dynamics on the mountain Elbrus was a drop of the water level and corresponding decrease of the lake areas in winter that was related to existence of the groundwater runoff into fractured volcanic rocks. At present, moraine dams of lakes and areas of the surface water runoff from the lakes are in stable condition due to which there is no threat of a lake outburst. However, the potential threat of outburst still remains because of high seismicity and possible volcanic activity in this region.